THE POLITICAL ECONOMY OF PLATFORM WORK: THE CASE OF DRIVERS AND COURIERS - Gontijo, Laura Valle (AoIR Selected Papers of Internet Research, 2026)
Platform work challenges Marxist academics. The main question that arises is: does platform work create value? Some authors claim not only that the work performed by platform workers creates value, but also that the activity of users on Facebook and Instagram, for instance, is a source of value (Fuchs, 2014). This perspective, however, has already been heavily criticized by theorists affiliated with the theory of value, with whom we agree (Kangal, 2014; Bolaños & Vieira, 2014; Comor, 2015).There are also those who argue that the theory of value is not capable of explaining platform work (Arvidsson & Colleoni, 2012). And there are those who claim that digital platforms are purely rent-seeking companies, an expression of the parasitic nature of current capitalism (Dowbor, 2024; Christophers, 2020).